Physiological roles of calcineurin in Saccharomyces cerevisiae with special emphasis on its roles in G2/M cell-cycle regulation - Miyakawa, T.(Hiroshima Univ. (Japan)); Mizunuma, M (Bioscience, biotechnology, and biochemistry, 2007)
Calcineurin, a highly conserved Casup(2+)/CaM-dependent protein phosphatase, plays key regulatory roles in diverse biological processes from yeast to humans. Genetic and molecular analyses of the yeast model system have proved successful in dissecting complex regulatory pathways mediated by calcineurin. Saccharomyces cerevisiae calcineurin is not essential for growth under laboratory conditions, but becomes essential for survival under certain stress conditions, and is required for stress-induced expression of the genes for ion transporters and cell-wall synthesis. Yeast calcineurin, in collaboration with a Mpk1 MAP kinase cascade, is also important in Gsub(2) cell-cycle regulation due to its action in a checkpoint-like mechanism. Genetic and molecular analysis of the Casup(2+)-dependent cell-cycle regulation has revealed an elaborate mechanism for the calcineurin-dependent regulation of the Gsub(2)/M transition, in which calcineurin multilaterally activates Swe1, a negative regulator of the Cdc28/Clb complex, at the transcriptional, posttranslational, and degradation levels.